2021
DOI: 10.3390/ani11030670
|View full text |Cite
|
Sign up to set email alerts
|

B-Mode and Contrast Enhanced Ultrasonography Features of Gastric Inflammatory and Neoplastic Diseases in Dogs

Abstract: Canine gastric disorders are common in veterinary clinical practice and among these neoplasms require rapid identification and characterization. Standard ultrasound (US) is the imaging modality of choice for gastric wall assessment. The aim of this prospective study is to describe the specific B-mode and contrast enhanced US (CEUS) features of normal, inflammatory, and neoplastic gastric wall in dogs. B-mode US and CEUS of the stomach were performed in anesthetized dogs with or without gastric disorders. Gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…1,6,9,14 Simeoni et al in a recent study, comparing B-mode and contrast-enhanced ultrasonography, did not find specific features to discriminate between the different gastric tumours. 22 Regarding the appearance of GL on CT, there are similarities with human patients and other veterinary reports, where GLs are well-defined lesions, isoattenuating and homogeneous (dogs: 51 ± 3 HU; humans: 69.4 ± 12 HU) with low-tointermediate post-contrast enhancement, similar to that seen in the cases presented here, taken from the nonmineralised areas in our patients. 15 Tanaka et al in 2019 reported the presence of two GL, which showed heterogeneous enhancement, due to what they believed was the presence of mineralisation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1,6,9,14 Simeoni et al in a recent study, comparing B-mode and contrast-enhanced ultrasonography, did not find specific features to discriminate between the different gastric tumours. 22 Regarding the appearance of GL on CT, there are similarities with human patients and other veterinary reports, where GLs are well-defined lesions, isoattenuating and homogeneous (dogs: 51 ± 3 HU; humans: 69.4 ± 12 HU) with low-tointermediate post-contrast enhancement, similar to that seen in the cases presented here, taken from the nonmineralised areas in our patients. 15 Tanaka et al in 2019 reported the presence of two GL, which showed heterogeneous enhancement, due to what they believed was the presence of mineralisation.…”
Section: Discussionsupporting
confidence: 87%
“…Simeoni et al. in a recent study, comparing B‐mode and contrast‐enhanced ultrasonography, did not find specific features to discriminate between the different gastric tumours 22 …”
Section: Discussionmentioning
confidence: 91%
“…Other authors mentioned that focal gastric wall thickness with loss of the normal wall layering may suggest gastric neoplasms [63]. Those features (to a much lesser extent) can be observed in cases of inflammatory conditions, with the exception of the involvement of lymph nodes and steatites [62].…”
Section: Gastrointestinal Tractmentioning
confidence: 99%
“…Gastric neoplasia in dogs can be characterized using B-mode ultrasonography as severe gastric wall thickening (exceeding 1.2 cm), marked loss of the wall layering, and involvement of adjacent structures (i.e., regional lymphadenomegaly and steatites) [62]. Other authors mentioned that focal gastric wall thickness with loss of the normal wall layering may suggest gastric neoplasms [63].…”
Section: Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation